A high-performance lithium-air battery cathode catalyst and preparation method thereof

The preparation of Fe3O4/La0.96Fe1-xMoxO3 composite catalyst by doping Mo atoms solved the problem of poor conductivity of lanthanum ferrite and significantly improved the performance of lithium air batteries.

CN119542444BActive Publication Date: 2025-03-28JILIN UNIVERSITY
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510096832.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-01-22
Publication Date
2025-03-28
Estimated Expiration
2045-01-22

AI Technical Summary

Technical Problem

The existing lanthanum ferrite catalysts have poor electrical conductivity, which limits the performance of lithium air batteries.

Method used

Fe3O4/La0.96Fe1-xMoxO3 composite catalyst of nanoparticles was prepared by sol-gel method, and doping Mo atoms to improve the conductivity of perovskite oxides.

Benefits of technology

The specific capacity and cyclic stability of lithium air batteries are significantly improved, and the catalytic activity and conductive properties are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119542444B_ABST
    Figure CN119542444B_ABST
Patent Text Reader

Abstract

A high-performance lithium-air battery cathode catalyst and a preparation method thereof, belonging to the technical field of lithium-air batteries. The lithium-air battery cathode catalyst of the present invention is a transition metal oxide Fe3O4 and a perovskite oxide La 0.96 Fe 1‑x Mo x The composite material is composed of lanthanum ferrite and iodine. The catalyst exists in the form of nanoparticles, the size of the nanoparticles is 20-80nm, and the molar percentage of the transition metal oxide in the catalyst is 3-8%. The present invention aims at the defect of poor conductivity of lanthanum ferrite itself. First, a gel is obtained by a sol-gel method, and then the gel is ashed at high temperature in a blast drying oven to obtain a precursor. Finally, the precursor is annealed in a tubular furnace with a reducing atmosphere to obtain a final sample. The preparation method of the present invention is simple, efficient and controllable, and the activity of the obtained catalyst is greatly improved compared with the unmodified catalyst. The specific capacity and cycle stability of the lithium-air battery assembled with it are significantly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of lithium-air batteries, and in particular relates to a high-performance lithium-air battery positive electrode catalyst and a preparation method thereof. Background Art

[0002] As the world's demand for electrical energy storage and conversion systems soars, it has driven the exploration of new energy storage devices such as metal-air batteries. The theoretical energy density of lithium-air batteries is higher than 5000 Wh kg -1 , with a theoretical open circuit voltage of 2.96 V, electric vehicles using these batteries could have a driving range of more than 550 km. Lithium-oxygen batteries (LOBs) consist of a metallic lithium anode, a catalyst, and a conductive current collector, and a cathode containing Li. + The aprotic electrolyte composition of LOBs, the oxygen reduction reaction (ORR) and oxygen evolution reaction (OER) occurring at the cathode dominate the discharge and charge processes. Although LOBs have great prospects due to their high theoretical energy density, several key issues need to be overcome to realize their application in reality. Specifically, the insulating discharge products of Li2O2 covering the cathode surface block the diffusion paths of oxygen and electrolyte ions, which can lead to electrical passivation on the cathode, especially at high current density, resulting in large overpotentials, limiting the capacity of LOBs. The reactive species generated during the cycling process can cause electrolyte decomposition and electrode corrosion, thus terminating the battery life. Therefore, it is necessary to develop high-performance cathode catalysts for lithium-air batteries to solve this problem.

[0003] When used as air cathodes for LOBs, perovskite oxides ABO3 have great potential for application due to their high catalytic activity for oxygen reduction reaction (ORR) and oxygen evolution reaction (OER). Their tunable composition, different structures, and unique electronic properties allow flexible manipulation of their catalytic activity. However, perovskites themselves have the characteristics of poor conductivity, such as LaFeO3, and the introduction of impurity atoms in the LaFeO3 lattice can change its band gap. For example, the incorporation of elements such as Sr, Ca, or Ru can form solid solutions. Doping can change the electronic structure, carrier concentration, and the entire crystal field environment, resulting in changes in the band gap energy. Composite catalysts can increase the surface area, improve electron transfer, and provide additional active sites for electrocatalytic reactions. The efficiency and activity of the LFO system can be further improved by composite nanoparticles with LFO. Summary of the invention

[0004] The technical problem to be solved by the present invention is to improve the problem of poor conductivity of the existing lanthanum ferrite as a catalyst, thereby providing a high-performance lithium-air battery positive electrode catalyst and a preparation method thereof.

[0005] The present invention aims to modify the defect of poor conductivity of lanthanum ferrite itself by doping with heterogeneous atoms. First, a gel is obtained by a sol-gel method, and then the gel is ashed at high temperature in a blast drying oven to obtain a precursor, and finally the precursor is annealed in a tubular furnace with a reducing atmosphere to obtain a final sample. The preparation method of the present invention is simple, efficient and controllable, and the activity of the obtained catalyst is greatly improved compared with the unmodified catalyst. The specific capacity and cycle stability of the lithium-air battery assembled with it are significantly improved.

[0006] The high-performance lithium-air battery cathode catalyst of the present invention is composed of transition metal oxide Fe3O4 and perovskite oxide La 0.96 Fe 1-x Mo x The catalyst is in the form of nanoparticles, the size of the nanoparticles is 20-80 nm, and the molar percentage of the transition metal oxide in the catalyst is 3-8%.

[0007] The method for preparing a high-performance lithium-air battery cathode catalyst of the present invention comprises the following steps:

[0008] (1) Gel prepared by sol-gel method:

[0009] The raw materials La(NO3)3‧xH2O, Fe(NO3)3‧9H2O and (NH4)6Mo7O were mixed in an atomic stoichiometric ratio of 0.85:0.9~1.0:0.05~0.1. 24 4H2O was added to 3mL ultrapure water and stirred to dissolve, then 1~2 g citric acid was added to the resulting mixed solution, and after dissolution, 0.8~1.5 mL ethylene glycol was added, and stirred at room temperature for 0.2~1 hour until the solution was mixed evenly, and then the resulting solution was heated at 70~90 ℃ to form a gel; in 3mL ultrapure water, the concentration range of La(NO3)3‧xH2O was 0.6~0.8 mol / L;

[0010] (2) Obtaining the precursor:

[0011] The gel obtained in step (1) was heated to 180-220 o C for 5 to 8 hours to obtain a sponge-like precursor;

[0012] (3) Preparation of positive electrode catalyst for lithium-air battery:

[0013] The sponge-like precursor obtained in step (2) is ground and pulverized, and then annealed in a reducing atmosphere to obtain the high-performance lithium-air battery cathode catalyst Fe3O4 / La 0.96 Fe 1-x Mo x O3, x = 0.05~0.10;

[0014] Preferably, the reducing atmosphere in step (3) is a mixed atmosphere of H2 and Ar, wherein the volume percentage of H2 is 1.5-3.0%.

[0015] Preferably, in step (3), the annealing temperature is 700-800° C., and the annealing time is 3-6 hours.

[0016] The technical solution of the present invention has the following advantages:

[0017] The present invention synthesizes a transition metal oxide-perovskite oxide composite material through a precursor one-step method after a large number of controlled variable experiments, and the preparation method is simple; the present invention successfully dopes Mo atoms into the perovskite structure, solves the problem that high-valent metal ions are difficult to dope into perovskite, and the doping of Mo atoms improves the disadvantage of poor conductivity of perovskite; the present invention applies the obtained transition metal oxide-perovskite oxide composite material as a positive electrode catalyst to a lithium-air battery reaction, and the improvement of its conductivity plays an important role in improving the catalytic activity of the lithium-air battery, and the formation of the composite material catalyst further enhances the catalytic effect on the battery reaction. Compared with the undoped composite material catalyst, the specific capacity properties and cycle stability of the battery are greatly improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0019] Figure 1 The x-ray diffraction patterns of the products of Comparative Example 1, Example 1, Example 2 and Fe3O4 powder of the present invention are shown in FIG.

[0020] Figure 2 Transmission electron microscope images of the products of Comparative Example 1, Example 1 and Example 2 of the present invention;

[0021] Figure 3 The scanning electron microscope image (upper figure) and the point scanning mode energy spectrum (lower figure) of the products of Comparative Example 1, Example 1 and Example 2 of the present invention;

[0022] Figure 4 The lithium-air battery with the product powders of Comparative Example 1, Example 1 and Example 2 as positive electrode catalyst at 100 mA g -1 , 200 mA g -1 and 500 mA g -1Current density, discharge-charge curves in the voltage range of 2.5~4.4V, and capacity retention bar graphs;

[0023] Figure 5 The lithium-air battery with the product powders of Comparative Example 1, Example 1 and Example 2 as positive electrode catalyst at 200 mA g -1 Current density, 500 mAh g -1 Cyclic stability curve under cut-off capacity and overpotential curve of first cycle charge and discharge. DETAILED DESCRIPTION

[0024] In order to better understand the essence of the present invention, the present invention is further described below in conjunction with specific embodiments. Any product identical or similar to the present invention obtained by anyone under the inspiration of the present invention or by combining the features of the present invention with other prior arts shall fall within the protection scope of the present invention.

[0025] If no specific experimental steps or conditions are specified in the examples, the experiments can be carried out according to the conventional experimental steps or conditions described in the literature in the art.

[0026] Comparative Example 1: This comparative example provides a lithium-air battery positive electrode catalyst, and its preparation method is as follows:

[0027] (1) Gel prepared by sol-gel method:

[0028] Add 0.8123g La(NO3)3‧xH2O and 1.01g Fe(NO3)3‧9H2O to 3mL ultrapure water and stir to dissolve. Then add 1.5g citric acid to the mixed solution, add 1mL ethylene glycol after dissolution, and stir at room temperature for 0.5 hours until the solution is mixed evenly. Then transfer the solution to a heating mantle and heat at 80℃ until a gel is formed.

[0029] (2) Obtaining the precursor:

[0030] Place the gel obtained in step (1) into a 200 o C in an oven for 6 hours to obtain a sponge-like precursor;

[0031] (3) Preparation of composite catalysts:

[0032] The sponge-like precursor obtained in step (2) was ground and annealed at 750°C for 4 hours in a tube furnace under a 2% H2 / 98% Ar (volume percentage) atmosphere to obtain a transition metal oxide-perovskite oxide composite material as a high-performance lithium-air battery positive electrode catalyst, with a product mass of 0.6 g. The size of the nanoparticles was about 30 nm, and the molar ratio of the transition metal oxide to the catalyst was about 5%.

[0033] Example 1: This example provides a high-performance lithium-air battery cathode catalyst, and its preparation method is as follows:

[0034] (1) Gel prepared by sol-gel method:

[0035] 0.8123g La(NO3)3‧xH2O, 0.9595g Fe(NO3)3‧9H2O and 0.0221g (NH4)6Mo7O 24 ·4H2O was added to 3 mL of ultrapure water and stirred to dissolve; then 1.5 g of citric acid was added to the obtained mixed solution, and 1 mL of ethylene glycol was added after dissolution, and stirred at room temperature for 0.5 hour until the solution was mixed uniformly; then the solution was transferred to a heating mantle and heated at 80°C to form a gel.

[0036] (2) Obtaining the precursor: same as in Comparative Example 1;

[0037] (3) Preparation of composite catalyst: As in Comparative Example 1, a transition metal oxide-perovskite oxide composite material as a high-performance lithium-air battery cathode catalyst was obtained, with a product mass of 0.6 g. The size of the nanoparticles was about 30 nm, and the molar ratio of the transition metal oxide to the catalyst was about 5%.

[0038] Example 2: This example provides a high-performance lithium-air battery cathode catalyst, and its preparation method is as follows:

[0039] (1) Gel prepared by sol-gel method:

[0040] 0.8123g La(NO3)3‧xH2O, 0.9090g Fe(NO3)3‧9H2O and 0.0442g (NH4)6Mo7O 24 ·4H2O was added to 3mL ultrapure water and stirred to dissolve; then 1.5g of citric acid was added to the obtained mixed solution, and after dissolution, 1mL of ethylene glycol was added and stirred at room temperature for 0.5 hours until the solution was mixed evenly; then the solution was transferred to a heating mantle and heated at 80°C until a gel was formed;

[0041] (2) Obtaining the precursor: same as in Comparative Example 1;

[0042] (3) Preparation of composite catalyst: As in Comparative Example 1, a transition metal oxide-perovskite oxide composite material as a high-performance lithium-air battery cathode catalyst was obtained, with a product mass of 0.6 g. The size of the nanoparticles was about 30 nm, and the molar ratio of the transition metal oxide to the catalyst was about 5%.

[0043] The catalyst obtained in Comparative Example 1 was recorded as LFO, the catalyst obtained in Example 2 was recorded as 05LFMO, and the catalyst obtained in Example 3 was recorded as 10LFMO.

[0044] The inductively coupled plasma test data of the products of Comparative Example 1, Example 1 and Example 2 are shown in Table 1. According to the data in Table 1, we can obtain the atomic ratio of the entire composite system through calculation.

[0045] Table 1: Inductively coupled plasma test data of products

[0046]

[0047] like Figure 1 As shown, it is the XRD curve diagram of Fe3O4, LFO, 05LFMO and 10LFMO, where Figure 1 (b) Yes Figure 1 (a) is an enlarged view of a local area; it can be seen that the diffraction peaks of LFO, 05LFMO and 10LFMO are basically consistent with the standard PDF card of perovskite LaFeO3 (JCPDS No. 742203), but there are impurity peaks at around 30.2° and 35.8°, and the peak intensity is very low. This shows that the main body of the LFO, 05LFMO and 10LFMO samples is a perovskite structure phase. We searched based on the position of the impurity peaks and the chemical composition elements and found that these peaks are consistent with the standard PDF card of Fe3O4 (JCPDS No. 750449), which shows that the synthesized samples are metal oxide Fe3O4 and perovskite oxide La 0.96 Fe 1-x Mo x O3 composite solid.

[0048] High-resolution transmission electron microscopy imaging tests, such as Figure 2 shown. Figure 2 (a) The LFO sample shows clear lattice fringes, with a lattice spacing of 0.28 nm, which corresponds to the (112) crystal plane of the perovskite LaFeO3. In addition, we also measured lattice fringes with a lattice spacing of 0.24 nm, which is attributed to the (222) crystal plane of Fe3O4. Figure 2 (b) The 05LFMO sample shows the same results. Figure 2 In the 10LFMO sample (c), in addition to the lattice spacing of the perovskite (112) crystal plane lattice stripes of 0.28 nm, a lattice stripe with a lattice spacing of 0.21 nm was also measured, which corresponds to the (400) crystal plane of Fe3O4. The results of high-resolution transmission and XRD measurements jointly confirmed that the sample we synthesized is a metal oxide Fe3O4 and a perovskite oxide La 0.96 Fe1-x Mo x O3 composed of composite solid.

[0049] The morphology of the samples was characterized. Figure 3 (a) corresponds to proportion 1, where Figure 3 (b) corresponds to Example 1, wherein Figure 3 (c) corresponds to Example 2; Figure 3 As shown in the figure above, we can see that the sample surface is very rough and there are granular substances generated, which may be the second phase Fe3O4 generated. In order to measure the atomic ratio more accurately, we selected the flat area in the figure above for EDX point scanning, and the results are shown in Figure 3 In the figure below, according to calculation, the atomic ratio of LFO, 05LFMO and 10LFMO is La 0.96 FeO3、La 0.96 Fe 0.94 Mo 0.06 O3 and La 0.97 Fe 0.91 Mo 0.09 O3, which is the measured element ratio of the main body of perovskite. 0.97 Fe 0.91 Mo 0.09 The difference between the La content of O3, 0.97 and 0.96, is within the error range of experimental testing.

[0050] The samples were tested by ICP, and the test results are shown in Table 1. After calculation, we obtained the element ratio of the samples. La:Fe = 0.83:1 in LFO, La:Fe:Mo = 0.84:0.94:0.06 in 05LFMO and La:Fe:Mo = 0.83:0.90:0.10 in 10LFMO, which is basically consistent with our feed ratio. Combining the ICP test results with the SEM-EDX test results ( Figure 3 ), according to the difference in the ratio of La and Fe elements, we can calculate the two phases of Fe3O4 and La 0.96 Fe 1-x Mo x O3, is 0.05:1. It can be seen that the content of the second phase is very small, and the main phase is still perovskite oxide. The atomic ratio obtained by ICP data includes the second phase Fe3O4, so the proportion of La will be reduced. 0.96 FeO3、La 0.96 Fe 0.94 Mo 0.06 O3 and La 0.97 Fe 0.91 Mo 0.09The ratio of the two phases is calculated based on the degree to which the La element is reduced in O3.

[0051] The capacity performance of the battery was characterized, such as Figure 4 As shown in the figure, LFO, 05LFMO and 10LFMO were tested for their first cycle constant current cutoff voltage specific capacity under different current density conditions. -1 At a current density of Figure 4 (a)), with specific capacities of 7650.3, 8507.6, and 9461.1 mAh g, respectively. -1 . at 200 mA g -1 At a current density of Figure 4 (b)), with specific capacities of 6360.5, 7274.5, and 7463.5 mAh g, respectively. -1 and at 500 mA g -1 At a current density of Figure 4 (c)), with specific capacities of 1645.0, 2442.7, and 5419.0 mAh g, respectively. -1 At different current densities, the specific capacity increases with the amount of Mo doping, which shows that Mo doping can effectively increase the number of active sites for the reaction. We also processed the battery rate performance, such as Figure 4 As shown in (d), at high current density, 10LFMO can still show excellent capacity retention, which is due to the improvement of the conductivity of the catalyst itself, and also shows that the stability of the catalytic activity of the catalyst has been enhanced.

[0052] The stability of the battery was characterized. Figure 5 The LFO, 05LFMO and 10LFMO shown in the figure are at a current density of 200 mAg -1 , cut-off capacity 500 mAh g -1 The constant current cut-off capacity cycle test was conducted under the conditions of 1000 MHz. Compared with the 32 cycles of LFO and the 66 cycles of 05LFMO, 10LFMO showed the best stability, with the number of cycles reaching 90 ( Figure 5 (a)) This improvement in cycling stability is closely related to the reversible generation and decomposition of the discharge product lithium peroxide, which is also a reflection of the catalyst's promotion of the redox reaction kinetics. To this end, we further tested the battery's kinetics. We conducted a series of experiments on LFO, 05LFMO, and 10LFMO at a current density of 200 mA g -1 , cut-off capacity 500 mAh g -1 The first cycle constant current cut-off capacity discharge-charge test was carried out under the conditions ( Figure 5(b) The results show that although the three catalysts show similar discharge platforms, the overpotential during the charge process is effectively reduced with the doping of Mo ions.

[0053] Obviously, the above examples are only examples for clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from them are still within the protection scope of the invention.

Claims

1. A method for preparing a high-performance lithium-air battery cathode catalyst, characterized in that: The steps are as follows: (1) Gel prepared by sol-gel method: The raw materials La(NO3)3‧xH2O, Fe(NO3)3‧9H2O and (NH4)6Mo7O were mixed in an atomic stoichiometric ratio of 0.85:0.9~1.0:0.05~0.

1. 24 4H2O was added to 3mL ultrapure water and stirred to dissolve, then 1~2 g citric acid was added to the resulting mixed solution, and after dissolution, 0.8~1.5 mL ethylene glycol was added, and stirred at room temperature for 0.2~1 hour until the solution was mixed evenly, and then the resulting solution was heated at 70~90 ℃ to form a gel; in 3mL ultrapure water, the concentration range of La(NO3)3‧xH2O was 0.6~0.8 mol / L; (2) Obtaining the precursor: The gel obtained in step (1) was heated to 180-220 o C for 5 to 8 hours to obtain a sponge-like precursor; (3) Preparation of positive electrode catalyst for lithium-air battery: The sponge-like precursor obtained in step (2) is ground and pulverized, and then annealed in a reducing atmosphere to obtain the high-performance lithium-air battery cathode catalyst Fe3O4 / La 0.96 Fe 1-x Mo x O3, x=0.05~0.

10.

2. The method for preparing a high-performance lithium-air battery cathode catalyst according to claim 1, characterized in that: In step (3), the reducing atmosphere is a mixed atmosphere of H2 and Ar, wherein the volume percentage of H2 is 1.5-3.0%.

3. The method for preparing a high-performance lithium-air battery cathode catalyst according to claim 1, characterized in that: In step (3), the annealing temperature is 700-800°C and the annealing time is 3-6 hours.

4. A high-performance lithium-air battery cathode catalyst, characterized in that: The invention is prepared by the preparation method according to any one of claims 1, 2 or 3.

5. A high-performance lithium-air battery cathode catalyst as claimed in claim 4, characterized in that: It is composed of transition metal oxide Fe3O4 and perovskite oxide La 0.96 Fe 1-x Mo x The catalyst is in the form of nanoparticles with a size of 20-80 nm, and the molar percentage of transition metal oxide in the catalyst is 3-8%.

Citation Information

Patent Citations

  • Double-perovskite structure catalyst material for cathode of lithium air battery and preparation method of catalyst material

    CN103545537A

  • Doped lanthanum ferrite material for solid oxide fuel cell

    CN109616673A